Glucose Metabolism: The Metabolic Signature of Tumor Associated Macrophage - Zhang, Qi; Wang, Junli; Yadav, Dipesh Kumar; Bai, Xueli; Liang, Tingbo (Frontiers in Immunology, 2021)
Macrophages exist in most tissues of the body, where they perform various functions at the same time equilibrating with other cells to maintain immune responses in numerous diseases including cancer. Recently, emerging investigations revealed that metabolism profiles control macrophage phenotypes and functions, and in turn, polarization can trigger metabolic shifts in macrophages. Those findings implicate a special role of metabolism in tumor-associated macrophages (TAMs) because of the sophisticated microenvironment in cancer. Glucose is the major energy source of cells, especially for that of TAMs. However, the complicated association between TAMs and their glucose metabolism is still unclearly illustrated. Here, we review the most important and advanced field of macrophage and glucose metabolism, discussing the significant transformations that occurs in tumor progression and conceivable guiding therapy targeting TAMs.